2015
DOI: 10.1002/hed.24359
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma: Do you know your guidelines?

Abstract: The pathogenesis of MCC has recently been impacted with the discovery of the Merkel cell polyomavirus (MCPyV). Research to establish targeted and immunologic therapeutic options are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 118 publications
(273 reference statements)
0
5
0
Order By: Relevance
“…More VN- and VP-MCC should be scrutinized to establish whether STING is specifically silenced in the VP-MCC and the potential role of T antigens in silencing STING should be explored. Postsurgical adjuvant radiation is common in the treatment of MCC patients and although adjuvant radiotherapy can improve locoregional control with reduced recurrence rate of the tumor, it may not affect overall survival [ 216 , 217 , 218 , 219 ]. Whether VN- and VP-MCC patients display different sensitivity to radiation is not known, but a previous study had shown that absence of STING impaired radiation-mediated tumor regression [ 220 ].…”
Section: Immune Evasion Of Vp-mccmentioning
confidence: 99%
“…More VN- and VP-MCC should be scrutinized to establish whether STING is specifically silenced in the VP-MCC and the potential role of T antigens in silencing STING should be explored. Postsurgical adjuvant radiation is common in the treatment of MCC patients and although adjuvant radiotherapy can improve locoregional control with reduced recurrence rate of the tumor, it may not affect overall survival [ 216 , 217 , 218 , 219 ]. Whether VN- and VP-MCC patients display different sensitivity to radiation is not known, but a previous study had shown that absence of STING impaired radiation-mediated tumor regression [ 220 ].…”
Section: Immune Evasion Of Vp-mccmentioning
confidence: 99%
“…Merkel cell carcinoma (MCC) is a rare but highly aggressive skin cancer occurring predominantly in elderly and immunosuppressed patients. The tumor shows a high propensity to metastasize, which is reflected in a poor 5 year survival rate [1][2][3][4][5]. The majority of MCCs (~60-80% in the northern hemisphere) are causally linked to infection with Merkel cell polyomavirus (MCPyV).…”
Section: Introductionmentioning
confidence: 99%
“…The poor outcomes in patients with metastatic MCC calls for more efficacious treatment options in the new horizon of precision medicine. Wide local excision is the primary treatment for localized primary MCC requiring negative margins of 1 to 2 cm . While there are mixed recommendations regarding postsurgical adjuvant radiation, this therapy remains the current guideline as the standard of care with several studies demonstrating reduced recurrence and improved survival .…”
Section: Discussionmentioning
confidence: 99%
“…Wide local excision is the primary treatment for localized primary MCC requiring negative margins of 1 to 2 cm . While there are mixed recommendations regarding postsurgical adjuvant radiation, this therapy remains the current guideline as the standard of care with several studies demonstrating reduced recurrence and improved survival . In patients who are not surgical candidates, radiotherapy alone or combined with systemic therapy has shown to extend life to some degree.…”
Section: Discussionmentioning
confidence: 99%